Promoting Effect of Fitness and Sports Application Based on Mobile Internet on the Formation of Fitness Habits of College Students: The Influence of Mobile Internet Sports Applications on College Students' Fitness Habits (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this present study rapidly development the science technology through that highly progress the mobile phone and Internet technology to use the online get information. Now we see the new era of smart phone used, in better and easy way to college students, health wellness, fitness and sports passionate peoples to learn exercise in mobile Internet. More application come into market and welcomed by colleges and sports passionate peoples. Therefore the author analyzes function and characteristic of available running application and combines the current college sports and students physical difficulties. The results show that the rational and scientific use of running application can stimulate students interest in exercise, improve the scientificity and persistence knowledge of exercise, reduce the incorrect movement of exercise improve the consciousness of exercise, and highly promote the development students, regular exercise habits effects.